Pengaruh Penggunaan Media Quizizz terhadap Motivasi Belajar Peserta Didik pada Mata Pelajaran Ekonomi di SMA Negeri 10 Palembang - Astuti, Dela; Fatimah, Siti (Jurnal Pendidikan Ekonomi, 2022)
Student learning motivation is a crucial factor in the success of educational processes, particularly in economics subjects that require active concept engagement. However, the lack of varied learning media often leads to low student interest. This study aimed to examine the influence of Quizizz media on enhancing student motivation at SMA Negeri 10 Palembang. The research employed an experimental method with a one-group pretest-posttest design. The sample consisted of 37 students from class XI IPS 5 selected through cluster random sampling. Instruments included a learning motivation questionnaire and observation sheet. The findings revealed an increase in the average motivation score from 59% to 81% after treatment, with a significant t-test value of 5.011 > 2.031. The coefficient of determination showed that 46% of the improvement was attributed to the use of Quizizz. The use of game-based interactive media such as Quizizz effectively stimulated student interest, engagement, and participation in online learning. Thus, teachers are encouraged to adopt innovative digital media to enhance learning quality and meet the demands of the digital era. Broader application across educational levels is recommended, with contextual adjustments as needed